Development of Financial Management Applications in Construction Companies Using the Extreme Programming Method - Sihombing, Denny Jean Cross (Teknik Informatika Universitas Pamulang, 2023)
This research aims to develop a financial management application for construction companies using the Extreme Programming (XP) Method. The construction industry often faces complexities in managing project finances, including cost tracking, cash control, and accurate financial reporting. The XP method was chosen as the primary approach due to its unique features, such as automated testing, close team collaboration, and flexibility in the face of change. The stages of application development, such as planning, design, coding, testing, integration, and launch, have been explained in detail. Continuous integration was used to ensure that any code changes were automatically tested and integrated into the main version of the application. The research results created a reliable and efficient financial management application that helps construction companies better manage projects, improve efficiency, and reduce financial risks. The main contribution of this research lies in applying the XP Method in developing a specialized financial application for the construction industry, providing a significant solution in addressing the complexity of financial management. In addition, this research provides valuable insights into the potential application of XP in various business contexts, making significant contributions to software developers and stakeholders in the construction industry.